Combination of Breast Care and Acupressure Interventions to Increase Milk Production and Breast Care in Breastfeeding Mothers - Eni Folendra Rosa; Aisyah Aisyah; Dina Oktavia; Nelly Rustiati (Lentera Perawat, 2025)
Breast milk is the optimal method to fulfil the nutritional needs of infants for optimal growth and development. However, limited milk production and ejection in the first days after delivery is often a barrier to exclusive breastfeeding. Breast engorgement in breastfeeding mothers is also a common challenge, which can hinder breastfeeding. This study used a case study design with a nursing process approach. The subjects were two breastfeeding mothers over 25 years old who experienced breast engorgement. The interventions provided included a combination of breast care and acupressure, which was carried out for four consecutive days with a duration of 20-30 minutes per session. Data were collected through observation, interview, and cheque sheet. The results showed a significant decrease in the intensity of breast engorgement and an increase in milk production in both subjects. In client I, the frequency of breastfeeding increased from 5 times to 9 times per day, and the frequency of baby's BAK increased from 5 times to 7 times per day. In client II, the frequency of breastfeeding increased from 6 times to 10 times per day, and the frequency of baby's BAK increased from 5 times to 7 times per day. Both clients reported decreased pain and increased comfort while breastfeeding. The combination of breast care and acupressure intervention is effective in overcoming the problem of breast engorgement and increasing milk production in breastfeeding mothers. The researcher suggested the combination of breast care and acupressure as part of breast care management in breastfeeding mothers.